2019
DOI: 10.1111/jgh.14642
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary iron and zinc intake and development of ulcerative colitis: A case–control study in Japan

Abstract: Background and Aim The prevalence of ulcerative colitis (UC) has been increasing in Japan. Trace elements, such as iron, zinc, magnesium, and copper, can cause digestive symptoms where there is a deficiency or excess. We focused on the dietary intake of trace elements and their associations with UC development. Methods A multicenter, hospital‐based case–control study was conducted in Japan. Cases were 127 newly diagnosed UC patients, and 171 age‐matched and sex‐matched hospital controls were recruited. We cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…First, iron enhances lipid peroxidation (converting PLOOH to the free radicals PLO• and PLOO•) through activation of LOX enzymes [32]. Increasing iron levels in the diet could directly increase cellular iron concentrations and the possibility of having UC [112,113]. Iron overload aggravated intestinal inflammation induced by DSS in rat model [114] In contrast, iron chelators could efficiently inhibit ROS generation and alleviate symptoms in IBD [115,116].…”
Section: Effects Of Dietary Nutrients and Phytochemicals On Ferroptosis And Gastric Diseasesmentioning
confidence: 99%
“…First, iron enhances lipid peroxidation (converting PLOOH to the free radicals PLO• and PLOO•) through activation of LOX enzymes [32]. Increasing iron levels in the diet could directly increase cellular iron concentrations and the possibility of having UC [112,113]. Iron overload aggravated intestinal inflammation induced by DSS in rat model [114] In contrast, iron chelators could efficiently inhibit ROS generation and alleviate symptoms in IBD [115,116].…”
Section: Effects Of Dietary Nutrients and Phytochemicals On Ferroptosis And Gastric Diseasesmentioning
confidence: 99%
“…Zinc deficiency is a very common symptomatic condition. According to a multicenter hospital-based case-control study conducted in Japan, higher doses of zinc taken by patients one year before the study period were associated with a decreased odds ratio for ulcerative colitis (UC), indicating that high zinc intake can protect against UC [43]. In a prospectively collected inflammatory bowel disease (IBD) registry study, zinc deficiency was associated with an increased risk of subsequent hospitalization, surgery, and disease-related complications in patients with IBD, Crohn's disease (CD), and UC [8].…”
Section: Zinc Deficiency Enhances Intestinal Inflammation Via Macrophmentioning
confidence: 99%
“…Interestingly, in previous studies by different groups, the administration of iron chelator was found to significantly reduce ROS in colonic tissues of UC patients and to ameliorate clinical symptoms and improve endoscopic presentations 9,10 . In contrast, high dietary iron supplements exacerbated UC symptoms in both patients and murine models 11,12 . These findings indicated the important effects of iron and ROS on the pathogenesis of UC.…”
Section: Introductionmentioning
confidence: 98%